PENGGUNAAN MEDIA TEKNOLOGI MELALUI APLIKASI QUIZIZZ UNTUK MENINGKATKAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN MATEMATIKA SEKOLAH DASAR - Rahayu, Etika Gustri; Nisa, Ana Fitrotun; Winarsih, Winarsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The aim of this research is to determine the effect of using Quizzizz on student learning outcomes in elementary school mathematics learning. This type of research is quantitative. The population in this study were all sixth grade students at SD Negeri I Sukomulyo, Rowokele District, Kebumen Regency, the sample used was 25 students. Data collection techniques include interviews, questionnaires and written tests. Before being applied to students, the instrument is analyzed first to determine the level of validity and reliability of the device to be used, so that the instrument is suitable for use. The results and discussion regarding the use of the quizizz application media on student learning outcomes in class VI Mathematics learning at SD Negeri I Sukomulyo show that using quizizz can improve student learning outcomes in mathematics learning in the classroom. Using Quizzizz in learning makes the learning process more enjoyable. Data collection using the pretest and posttest method on one competency took place over two meetings. The results of this research showed an increase in average learning outcomes in the pretest (learning not using Quizizz media) by 34% and post test (learning using Quizizz media) by 82%. Based on the value data presented, there is an increase in the learning outcomes of class VI students in using quizizz media in mathematics learning in elementary schools.